The impact of using smart applications, “Sehaty application”, on health care at primary Care Center in Al-Qurayat region - Ajina, Manal Abdulrhaman (Journal of Economic, Administrative and Legal Sciences, 2024)
The research aimed to investigate the impact of using smart applications, specifically the "Sehhaty" application, on healthcare in primary care centers in the Al Qurayyat province. The study used a descriptive-analytical methodology and relied on an electronic questionnaire as a tool for data collection. The study sample consisted of 213 residents of Al Qurayyat and 211 individuals from major cities. The study found that the most common method used to obtain healthcare services inside and outside the province was through the "Sehhaty" application, but the residents of Al Qurayyat were the least likely to use it. The study also found that the level of knowledge and ease of use of the application was slightly lower among residents of the province. Additionally, the study found that residents of the province benefited more from the services of the application and that residents of major cities were more satisfied with the application’s services. The most significant problem encountered by both residents of the province and major cities when using the application was the need for a high-speed internet connection. The study recommended several measures to optimize the use of the application.